2016
DOI: 10.3991/ijep.v6i4.6079
|View full text |Cite
|
Sign up to set email alerts
|

Applying Andragogy to Promote Active Learning in Adult Education in Russia

Abstract: Abstract-In this rapidly changing world of technology and economic conditions, it is essential that practicing engineers and engineering educators continue to grow in their skills and knowledge in order to stay competitive and relevant in the industrial and educational work space. This paper describes the results for a course that combined the best techniques of andragogy to promote active learning in a curriculum of chemistry education, in particular, chemistry laboratory education. This experience with two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…Despite the abovementioned, in general, studies selected for the analysis report positive students' attitudes towards this active learning method. The study in [128] revealed that this type of learning was perceived as beneficial and, moreover, increased students' interest and enthusiasm. An important finding, however, is that despite the positive feedback on active learning, where students are given more responsibility on controlling the learning process, they report that it was easier to grasp the course material when a slide presentation was also delivered [128].…”
Section: Reported Attitudes In Pjblmentioning
confidence: 99%
“…Despite the abovementioned, in general, studies selected for the analysis report positive students' attitudes towards this active learning method. The study in [128] revealed that this type of learning was perceived as beneficial and, moreover, increased students' interest and enthusiasm. An important finding, however, is that despite the positive feedback on active learning, where students are given more responsibility on controlling the learning process, they report that it was easier to grasp the course material when a slide presentation was also delivered [128].…”
Section: Reported Attitudes In Pjblmentioning
confidence: 99%
“…For instructors who teach adult students, the literature is evident on the importance of curriculum alignment in adult education. For instance, according to Sanger and Pavlova (2016), alignment along with the content's relevancy to life and experience, its emotional connection to the learner, and self-directed learning are all part of the principles of andragogy when discussing curricula. Another supporting argument on the value of aligning curriculum is that it adds to curriculum conversation efficacy (Shaltry, 2020).…”
Section: Aligning Curriculummentioning
confidence: 99%
“…Os princípios da andragogia incluem a capacidade de resolução de problemas, a observação da relevância do assunto pelo aprendiz adulto, aprendizado autodirigido, além de conexões emocionais com o episódio de ensino, englobando a capacidade de se divertir enquanto aprende e manter-se motivado frente ao objeto de estudo (Sanger, & Pavlova, 2016). Os artigos selecionados trazem em seus resultados, para além dos escores obtidos pelos alunos, que os jogos motivam mais os alunos a estarem imersos no episódio de ensino, e serem mais participativos e se interessarem mais sobre o tema pela abordagem ter sido trazida através do GBL, como relatam Guckian et al, (2019).…”
Section: Eficácia Da Estratégia De Gbl Na Aprendizagem Significativa ...unclassified